Challenges and achievements of the EU migration policy over the years - Clemente Soler, Juan Antonio; Rodríguez Guillén, David (Papeles de Europa, 2020)
This article analyses the EU measures deployed in migration by using a qualitative methodology for the selection of legislation and articles. The document analysis methodology structures the article in three parts: evolution of the area (1950- 2015). Analysis of the last EU legislative measures. Its external dimension. Although the article limits its scope to a legislative and institutional analysis, this work is very relevant, as immigration is an important topic in the political agenda. The analysis shows that the measures have been effective although some legislation needs to be finished for a phenomenon, which is constantly evolving.